KERJASAMA AUSTRALIA – INDONESIA MELALUI PROGRAM MAMPU UNTUK MENANGANI MASALAH KEKERASAN TERHADAP PEREMPUAN DI INDONESIA (STUDI KASUS 2017 – 2020) - Nadine Bertha Sagala Dendrobium; Den Yealta (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2023)
Violence against women includes any act of gender-based violence that causes or can result in physical, sexual or psychological harm or suffering to women, including threats of such acts, coercion and arbitrary deprivation of liberty, whether occurring in public or private life. In order to reduce the number of violence against women that occurs in Indonesia, Australia through an assistance program established by DFAT (Department of Foreign Affairs and Trade) has made a partnership with Indonesia and BAPPENAS. The purpose of this research is to find out the collaboration between Australia and Indonesia through MAMPU Program on dealing with violence against women cases in Indonesia. In this study, researchers used the concept of gender equality which is one of the concepts of human security to analyze the efforts made by MAMPU Program on handling cases of violence against women. The research method used in this research is qualitative with data collection techniques based on literature study. The data was obtained through the official website of the MAMPU Program, the official website of the Australian Embassy and the official website of the Ministry of National Development Planning/BAPPENAS, and the official website of Komnas Perempuan. The results of this study indicate that there is an implementation of Australia - Indonesia cooperation through MAMPU Program to handle cases of violence against women in Indonesia (2017 - 2020). As well as progress in access to services at MAMPU Partners, although this has not impact much to reduce the number of violence against women in Indonesia. Keywords: MAMPU, Gender Equality, Violence Against Women, Australia-Indonesia Cooperation